Discrete-event multiagent coordination : framework and algorithms - Pham, Manh Tung (2011)
This thesis proposes a formal design framework for three inter-agent coordination problems that have not been addressed in the literature: A fundamental coordination problem, a networked coordination problem and an on-line coordination problem. The problems arise when distributed agents need to interact and communicate among themselves in order to guarantee conformance to some inter-agent constraints that restrict their behaviors. These problems are formulated and addressed for a class of agents in a discrete-event behavioral formalism. The basic solution proposed is to equip agents with some distributed, local cooperation mechanism called coordination modules (CM's), by which they can compute their local coordinating actions in response to each other's information update. The framework developed supports the automated synthesis of CM's for discrete-event agents.